INDICES OF ENERGY METABOLISM AND ATP-ase ACTIVITY OF MYOSIN IN VESSELS OF NEWBORN RATS-DESCENDANTS OF PARENTS-"SMOKERS" - Юнусов В. Ю.; Мартинова С. М. (World of Medicine and Biology, 2014)
The aim of our research was to analyze ATP-ase activity of myosin, the content of ATP, ADP and CPK activity in the femoral artery and the aorta newborn rats-descendants "smokers" parents. Materials and methods. Ca2+-activated ATPase activity of myosin, CPK activity, the content of ATP and ADP in the aorta and the femoral artery of newborn rats with different variants for "tobacco smoking" parents were studied. The experiment was carried out on Wistar rats. Modeling of "tobacco smoking" was produced by placing rats in a specially designed chamber, where tobacco smoke from cigarettes Priluki was distributed. Animals were divided into four groups: 1) only females "smoked"; 2) only males "smoked"; 3) males and females "smoked"; 4) control. Females were placed in the chamber daily for 15 min within 1 month prior to mating and during pregnancy, males for 1 month prior to mating (daily). The intact animals from the control group were placed in similar conditions in the chamber that did not contain tobacco smoke. Newborn rats were removed from the experiment by decapitation under light ether anesthesia. Aorta and the fragments of the femoral artery were extracted. The vessels were cleaned from blood by chilled saline solution. They were frozen in liquid nitrogen, crushed to a powder consistency, homogenates in 0.32 M Tris-HCL buffer were prepared from them. Extraction of myosin and determination of Ca2+-activated ATP-ase activity of myosin was carried out according to the method described by Magrossian S. S. Determination of ATP content in the homogenates of the vessels was performed according to the method described by Eschenko N. E. Determination of CPK activity was carried out using a reagent kit from the company Filist-Diagnosticum (Dnepropetrovsk, Ukraine). The obtained data were processed using a special program SPSS for Windows. The method used of comparison of two averages on the basis of the t-criterion of Student was used. Results. Our research showed decreased contractility of the smooth muscle fibers of blood vessels when only mothers and both parents "smoked", as evidenced by the decrease in ATP-ase activity of myosin, CPK activity and decreasing the rate of ADP/ATP in the blood vessels. Changes are most pronounced among the male descendants when only mothers smoked, which seems to be due to toxic effect of tobacco on the fetus. Descendants whose fathers smoked have no changes in the studied parameters. Conclusions. The obtained results allow making the following conclusions. 1. "Tobacco smoking" of only mothers and both parents leads to changes in the contractility of the smooth muscle fibers of the aorta and femoral artery of rats descendants of both sexes, as evidenced by the decrease in ATPase activity of myosin, CPK activity and content of ATP in vessels of newborn rats. 2. Both in the femoral artery and in the aorta changes in indices of contractile myofibrils are more pronounced in the male offspring of smoking mothers. 3. When only males "smoked", the offspring has no changes in indices of contractile myofibrils, which, apparently, is due to the lack of toxic effects of tobacco on the fetus.